2013
DOI: 10.1016/j.ajhg.2013.10.004
|View full text |Cite|
|
Sign up to set email alerts
|

Global Analysis of DNA Methylation Variation in Adipose Tissue from Twins Reveals Links to Disease-Associated Variants in Distal Regulatory Elements

Abstract: Epigenetic modifications such as DNA methylation play a key role in gene regulation and disease susceptibility. However, little is known about the genome-wide frequency, localization, and function of methylation variation and how it is regulated by genetic and environmental factors. We utilized the Multiple Tissue Human Expression Resource (MuTHER) and generated Illumina 450K adipose methylome data from 648 twins. We found that individual CpGs had low variance and that variability was suppressed in promoters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
381
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(435 citation statements)
references
References 63 publications
44
381
1
1
Order By: Relevance
“…9 Gruenberg et al using 648 twins of European descent also reported a genetic heritability of 19% in adipose tissue. 16 Our genetic heritability estimate is more similar to the one reported by Garvin et al, which ranges from 2 to 16% in the MHC region in CD4 C lymphocytes of healthy monozygotic and dizygotic twins. 20 In this study, genetic heritability also varies by gene region types (CpG islands, 5 0 ends of genes, conserved noncoding regions, and randomly selected regions).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…9 Gruenberg et al using 648 twins of European descent also reported a genetic heritability of 19% in adipose tissue. 16 Our genetic heritability estimate is more similar to the one reported by Garvin et al, which ranges from 2 to 16% in the MHC region in CD4 C lymphocytes of healthy monozygotic and dizygotic twins. 20 In this study, genetic heritability also varies by gene region types (CpG islands, 5 0 ends of genes, conserved noncoding regions, and randomly selected regions).…”
Section: Discussionsupporting
confidence: 89%
“…More recently, studies using genome-wide DNA methylation array (Illumina 450K) have reported an average genetic heritability of 19% in peripheral blood leukocytes and 19% in adipose tissue. 9,16 Transgenerational similarity in DNA methylation levels has also been reported. 13 Several genome-wide association studies with methylation quantitative trait loci (mQTL) in both cis and trans locations have confirmed the genetic heritability of DNA methylation.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Subsequently, Grundberg et al performed a large-scale heritability analysis with the Illumina 450k array, including 97 MZ and 162 DZ twins and estimated the heritability for 344,092 methylation sites. In concordance with previous estimates, the overall heritability was estimated to be 19% [88].…”
Section: Heritability Of the Epigenomesupporting
confidence: 88%
“…Major changes in DNA-me distribution at promoters are a hallmark of cancer (13,16). However, in chronic diseases, such as diabetes and its complications, increasing evidence suggests the importance of DNA-me in regulatory regions, including putative enhancer regions in kidney tissues from patients with diabetic kidney disease (50), intronic enhancers in blood cells type 2 diabetes patients (51), and gene bodies/intergenic regions rather than promoters in adipose tissues from twins (52). The high percentage of DMLs in intergenic regions, introns, and 3′ UTRs in our study is in line with such reports.…”
Section: Discussionmentioning
confidence: 99%